Moral Resilience of Santri: Strategies of Pesantren Alumni Students in Preserving Ethical Integrity on Campus - Muhammad Rasyid Ridho; Mujahid Mujahid; Muhammad Zaini; Mohamad Agung Rokhimawan (Universitas Sebelas Maret, 2026)
In Indonesia, santri (pesantren students) who continue to urban Islamic universities undergo a notable cultural transition, moving from the structured communal life of the pesantren to academic life within a heterogeneous urban environment. Although Islamic universities uphold religious values and nurture a religious campus, external urban influences and the weakening of students' personal motivation to sustain worship after leaving communal supervision can reshape their moral experience. Understanding how santri alumni navigate this transition is crucial for Islamic higher education. This qualitative field study used an interpretive phenomenological approach to examine the moral resilience strategies of pesantren alumni at Universitas Islam Negeri Sunan Kalijaga Yogyakarta, positioning the campus as the locus rather than an object of evaluation. Data were gathered through in-depth interviews and participant observation with eight undergraduate students who had resided in pesantren for at least three years, plus three supporting informants. The findings revealed that the shift to a heterogeneous urban setting triggers culture shock, as evidenced in gender-mixed interactions and a perceived shift in peers' religious practices, which participants attribute to external influences rather than the institution. Rather than withdrawing physically, students exercise selective social filtering while maintaining inclusive academic engagement. Sufi values such as tawakal, patience, and ikhlas (sincere) serve as psychological stabilizers, while identity management is dualistic: some invoke their santri status as a moral resource, others conceal it to ease collective expectations. These findings yield a conceptual modification, Neo-Zuhud Urban (Open Practical Asceticism), reframing classical santri moral withdrawal as an inclusive practice enacted within, not apart from, public social life.